Market or Mandate? Exploring Synergistic Low‐Carbon Regulations and Green‐Biased Technological Progress - Wu, Xiaoxu; Zhu, Rui; Wang, Tengjiao; Chen, Yuhui (Managerial and decision economics, 2025)
ABSTRACT Green‐biased technological progress is a critical pathway for achieving low‐carbon development. This study investigates how command‐and‐control and market‐based low‐carbon regulations influence green‐biased technological progress from the perspective of policy combinations, providing policy recommendations for reducing global carbon emissions and designing efficient policy synergy pathways. The findings reveal a significant synergistic effect between command‐and‐control and market‐based low‐carbon regulations. Compared with single‐policy approaches, synergistic regulations more effectively promote green‐biased technological progress. The conclusion is robust across various tests. Mechanism analysis indicates that the synergistic regulations primarily enhance green‐biased technological progress by augmenting firm green investment intensity and facilitating industrial structure upgrading. Furthermore, command‐and‐control and market‐based low‐carbon regulations exhibit asymmetric impacts on green‐biased technological progress in cities with different characteristics. Compared to market‐based low‐carbon regulations, command‐and‐control low‐carbon regulations have a more pronounced effect in cities facing greater fiscal pressure, higher proportions of state‐owned assets, and a larger share of high‐energy‐consuming industries. These findings provide actionable insights for maximizing the combined effects of synergistic regulations, accelerating the green‐biased technological progress dividend through targeted collaborative governance models, and enhancing the diversified implementation of heterogeneous low‐carbon regulations.